Fusarochromanone Induces G1 Cell Cycle Arrest and Apoptosis in COS7 and HEK293 Cells - Gu, Ying; Chen, Xin; Shang, Chaowei; Singh, Karnika; Barzegar, Mansoureh; Mahdavian, Elahe; Salvatore, Brian A.; Jiang, Shanxiang; Huang, Shile (PLOS ONE, 2014)
Fusarochromanone (FC101), a mycotoxin produced by the fungus Fusarium equiseti, is frequently observed in the contaminated grains and feedstuffs, which is toxic to animals and humans. However, the underlying molecular mechanism remains to be defined. In this study, we found that FC101 inhibited cell proliferation and induced cell death in COS7 and HEK293 cells in a concentration-dependent manner. Flow cytometric analysis showed that FC101 induced G1 cell cycle arrest and apoptosis in the cells. Concurrently, FC101 downregulated protein expression of cyclin D1, cyclin-dependent kinases (CDK4 and CDK6), and Cdc25A, and upregulated expression of the CDK inhibitors (p21Cip1 and p27Kip1), resulting in hypophosphorylation of Rb. FC101 also inhibited protein expression of Bcl-2, Bcl-xL, Mcl-1 and survivin, and induced expression of BAD, leading to activation of caspase 3 and cleavage of PARP, indicating caspase-dependent apoptosis. However, Z-VAD-FMK, a pan-caspase inhibitor, only partially prevented FC101-induced cell death, implying that FC101 may induce cell death through both caspase-dependent and -independent mechanisms. Our results support the notion that FC101 executes its toxicity at least by inhibiting cell proliferation and inducing cell death.